(untitled) (London Journal of Research In Humanities and Social Sciences, 2026)
During the First World War, the practice of reciprocity through reprisals and maltreatment against prisoners of war led to the international law against such actions in the newly developed 1929 Geneva Convention Relative to the Treatment of Prisoners of War. Despite the new Convention, the practice of reciprocal treatment in the form of reprisals remained significant among belligerent states during the Second World War. Yet, it is important to understand how international conventions such as the Geneva Convention could be manipulated to pursue a course of reprisal action that would impact prisoners. Critically, the ability to manipulate the enemy through the treatment of their prisoners of war (POWs) established the British government’s attitude toward prisoner of war reprisals. Equally important, the Australian and Dominion governments’ response to the treatment of their Prisoners of War (POWs) during instances of reprisals and punishment as a sovereign government and member of the British Empire. How the Convention and reprisals against prisoners in POW camps were implemented, and the difference between punishment and reprisals is important. Although the punishment of shackling in November 1941, inflicted on Australian soldiers in Italian camps, violated international conventions as well as Italy’s military regulations. This act of shackling originated from an incident within the POW camp itself. It can be compared to the more widely recognised political reprisal known as the shacking crisis of 1942-1943. Analysing the ongoing violations of international conventions leading up to the shackling incidents and distinguishing between the two episodes is essential to understanding how belligerent governments manipulated the Convention to serve their national interests. Central to these events is the impact on prisoners in POW camps, who were particularly vulnerable; therefore, the actions in Italy and during the shacking crisis are comparable in this regard. However, during the crisis, Britain and Germany exploited prisoners of war as political instruments, transforming the episode of reprisal into a wartime weapon. A comprehensive review of the Geneva Convention, especially the articles concerning reprisals and the mistreatment of prisoners, in relation to British and Dominion forces, will illuminate the treatment of prisoners during the Second World War.